THE DIFFICULTIES IN TEACHING AND LEARNING THROUGH ONLINE CLASS DURING PANDEMIC COVID – 19 - Abdullah, Ainah Bt; Januarty, Restu (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2021)
This literature review is all about how difficult online class teaching and learning is during this pandemic covid – 19. This study is to know how teachers and students get some difficult time from this pandemic covid during the online class. The data and sources were taken from a few articles that explain the problem and solution of education in this pandemic period. The collected data is analyzed by using the qualitative method. The data collection and the result were carried out from a few published articles. This literature review also explains the difference between online class and offline class and what is demanding that teachers and students got from the online class and explain the solution is.